China’s rising maritime aspirations : impact on Beijing’s good-neighbour policy - Li, Mingjiang (2012)
The proceedings at the recent political congresses in Beijing indicate an emerging consensus in China on the need to safeguard and expand its maritime interests. This may defeat the government’s policy goal of improving relations with neighbouring countries.